Centres of rotation and osteological constraints on caudal ranges of motion in the sauropod dinosaur Giraffatitan brancai - Verónica Díez Díaz; Pasha A. van Bijlert; William Irvin Sellers; Mathew J. Wedel; Daniela Schwarz (Royal Society Open Science)
Archosaur tails are important appendages, not only for their biomechanical function but also for being behavioural tools that help the animal communicate and interact with its environment. Until recently, tails have been neglected in biomechanical analyses and were considered as a stiff (sometimes independent) unit; however, the tail’s role in movement is now increasingly being appreciated. In this work, we present detailed analyses of the ranges of motion of the amphicoelous anterior caudal series MB.R.2921 from the Late Jurassic sauropod Giraffatitan brancai from Tanzania. We discuss possible positions of the centres of rotation, potential osteological constraints and how they affect the mobility of the caudal series. Our results highlight the importance of considering haemal arches as functional units and osteological constraints in ventroflexion of the tail. Thorough range of motion analyses of the axial skeleton have the potential to yield novel insights into the functional morphology and behaviour of extinct animals.